BILATERAL MONETARY CREDIT SYSTEM AND ITS EFFECTS FOR DECENTRALIZATION OF THE MONETARY CREDIT SYSTEM - M. M. Rahimian (Вестник университета)
Many countries are subject to sanctions, often imposed by more developed countries due to political circumstances on the part of economic. In such circumstances, the development of a country under sanctions can be characterized by a number of features, such as lack of access to credit funds of the global banking system, difficulties in carrying out international banking operations, etc. However, the example of some countries, in particular Iran, shows the ex-istence of opportunities for the development of the monetary system in terms of sanctions. The development of the monetary system of the Islamic Republic of Iran at the expense of decentralization is characterized by universal practical examples of counteraction to sanctions, confirming the possibility of real counteraction from the state subjected to sanctions.